The Impact of Digital Transformation on Students’ Character Education - Fadilla, Dina Rizki; Bahar, Yolanda; Sari, Meylia; Salim, Agus; Sari, Rina Purnama (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2024)
Digital transformation brings significant changes in various aspects of life, including education. On the other hand, education is also responsible for shaping the personality of students, so researchers are interested in studying the impact of digital transformation on character development in students. This research aims to improve the quality of education by preventing negative habits of students or enhancing their positive habits. The method used in this research is descriptive qualitative research through interviews, observations, and documentation. The research results show that digital transformation has two simultaneous impacts, namely positive and negative impacts. This study concludes that the positive character of students is formed from their regular and disciplined positive habits, supported by parents and the school environment that also supervise them, whereas the negative character of students is formed from their undisciplined and difficult-to-manage negative habits due to the lack of supervision from parents or the school environment